Keanekaragaman dan Potensi Pemanfaatan Makroalga di Pesisir Pulau Tunda - Endang Sunarwati Srimariana; Mujizat Kawaroe; Dea Fauzia Lestari; Aditya Hikmat Nugraha (Jurnal Ilmu Pertanian Indonesia, 2020)
Macroalgae is one of the marine biological resources that has a potential to be utilized further by humans. This research aims to study macroalgae diversity and utilization potency by humans in the coastal area of Tunda Island. The study was conducted at 4 stations using the belt transect method. Results of this study indicated that there were 15 species of macroalgae found that came from 3 macroalgae classes, they were chlorophyceae, phaeophyceae, and rhodophycea. Macroalgae species that are often found are Padina minor, Halimeda macroloba, and Gracilaria salicornia. The highest macroalgae diversity was found at station 3 with a value of 2.44. Based on the type of macroalgae found in the field there are several macroalgae species that can be utilized, and the lack of information causes the low macroalgae utilization by the local community. Keywords: Biodiversity, Gracilaria salicornia, Halimeda macroloba, macroalgae, Padina minor